2007
DOI: 10.1158/0008-5472.can-07-1483
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor– and E2F-1–Targeted Thymoquinone Therapy for Hormone-Refractory Prostate Cancer

Abstract: Relapse of prostate cancer after androgen ablation therapy is hormone-refractory, with continued tumor growth being dependent on the androgen receptor (AR). E2F-1, a regulator of cell proliferation and viability, reportedly plays a role in the development of hormone-refractory prostate cancer. Thymoquinone is a component of Nigella sativa, an herb used for thousands of years for culinary and medicinal purposes in Asian and Middle Eastern countries and has been reported to have an antineoplastic effect both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(146 citation statements)
references
References 34 publications
(47 reference statements)
7
135
2
2
Order By: Relevance
“…It is reported that in prostate cancer PC3 cells, thymoquinone may suppress tumor angiogenesis and growth by downregulating AKT and extracellular signal-regulated kinase (ERK) signaling (17). Additionally, thymoquinone notably suppressed DNA synthesis and proliferation in prostate cancer LNCaP, C4-2B, DU145 and PC3 cell lines via inactivation of the androgen receptor (AR) and E2F1, a regulator of cell viability (18). In addition, it has been found that thymoquinone could potentiate the cytotoxic and pro-apoptotic effect of zoledronic acid (ZA) in prostate cancer PC3 and DU145 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in prostate cancer PC3 cells, thymoquinone may suppress tumor angiogenesis and growth by downregulating AKT and extracellular signal-regulated kinase (ERK) signaling (17). Additionally, thymoquinone notably suppressed DNA synthesis and proliferation in prostate cancer LNCaP, C4-2B, DU145 and PC3 cell lines via inactivation of the androgen receptor (AR) and E2F1, a regulator of cell viability (18). In addition, it has been found that thymoquinone could potentiate the cytotoxic and pro-apoptotic effect of zoledronic acid (ZA) in prostate cancer PC3 and DU145 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…T hy m o q u i n o n e ( 2 -i s o p ro py l -5 -m e t hy l -1 , 4 -benzoquinone) (Figure 1) is the main bioactive component of the volatile oil of the medical plant Nigella sativa (Black seed), and it has been shown to excrete anticancerous, antioxidant and anti-inflammatory activities both in vitro and in vivo (Worthen et al, 1998;Kaseb et al, 2007;Mansour et al, 2002;Chehl et al, 2009). Many previous reports have shown promising antitumor characteristics of thymoquinone (TQ) against different types of cancer cell lines in vitro, including human colorectal cancer cells (Gali-Muhtasib et al, 2004), myeloblastic leukemia cells (El-Mahdy et al, 2005), prostate cancer (Kaseb et al, 2007), pancreatic adenocarcinoma (Worthen et al, 1998) and ovarian and breast adenocarcinoma (Shoieb et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous reports have shown promising antitumor characteristics of thymoquinone (TQ) against different types of cancer cell lines in vitro, including human colorectal cancer cells (Gali-Muhtasib et al, 2004), myeloblastic leukemia cells (El-Mahdy et al, 2005), prostate cancer (Kaseb et al, 2007), pancreatic adenocarcinoma (Worthen et al, 1998) and ovarian and breast adenocarcinoma (Shoieb et al, 2003). The chemoprevention potential of TQ has been also recognized.…”
Section: Introductionmentioning
confidence: 99%
“…[32] TQ has also been reported to have anticarcinogenic effects by blocking tumor cell progression via apoptosis of cells in G1 phase of the cell cycle in breast, ovary, colorectal, osteosarcoma, fibrosarcoma, lung, and prostate cancers. [33][34][35][36][37] Effects of TQ on the peripheral nervous system were reported in 3 studies. [10,11] The first of these was performed in an experimental streptozotocin-induced diabetic neuropathy model.…”
Section: Discussionmentioning
confidence: 99%